2020
DOI: 10.23887/ijssb.v4i4.28156
|View full text |Cite
|
Sign up to set email alerts
|

Brand Loyalty and Repurchase Intention of a Coffee Brand: The Roles of Sensory Attributes, Functional Benefit, and Brand Ambassador

Abstract: The trend of drinking coffee has resulted in an increase of coffee consumption around the world, including Indonesia. This study investigates the roles of sensory attributes, functional benefit, and brand ambassador towards the intention to repurchase which leads to brand loyalty of Luwak White Koffie. This study uses a quantitative approach by using primary data and distributed questionnaires to 100 employees of various corporations in Jakarta. The data was analyzed through regression analysis. The result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
0
0
1
Order By: Relevance
“…Seventh, in this research it was found that product attributes have a positive but not significant influence on consumers' repurchase intention. This is in line with research conducted by Ririn et al, [42] and research by Pangaribuan et al [43], which shows that product attributes, both in the form of product packaging and sensory attributes, do not have a significant influence on product repurchase intention. This means that Indomaret consumers do not really consider the attributes of Indomaret private label products such as packaging, taste, aroma, color and other characteristics attached to the product to immediately decide to repurchase.…”
Section: The Influence Of Product Attributes On Repurchase Intentionsupporting
confidence: 91%
“…Seventh, in this research it was found that product attributes have a positive but not significant influence on consumers' repurchase intention. This is in line with research conducted by Ririn et al, [42] and research by Pangaribuan et al [43], which shows that product attributes, both in the form of product packaging and sensory attributes, do not have a significant influence on product repurchase intention. This means that Indomaret consumers do not really consider the attributes of Indomaret private label products such as packaging, taste, aroma, color and other characteristics attached to the product to immediately decide to repurchase.…”
Section: The Influence Of Product Attributes On Repurchase Intentionsupporting
confidence: 91%
“…Membangun relasi selain pembukaan gerai melalui marketing waralaba juga dengan pelayanan yang ramah dengan pelanggan yang berkunjung secara langsung. Customer relationship marketing memediasi kemasan unik dan minat berkunjung (Dhameria, 2014;Evandro Ernantyo & Febry, 2022;Pangaribuan et al, 2020). Sehingga hipotesis lima didukung.…”
Section: Customer Relationship Marketing Memediasi Kemasan Unik Dan M...unclassified